Microencapsulation of Green Coffee Beans (Coffea canephora) Extract using Whey Protein Concentrate - Husni, Muhammad Ali; Nugroho, Akhmad Kharis; Sulaiman, Teuku Nanda Saifullah; Fakhrudin, Nanang (Iraqi Journal of Pharmaceutical Sciences, 2022)
Coffee bean contains bioactive compounds including caffeine and chlorogenic acid (CGA) that have a stimulant effect and are used for combating fatigue and drowsiness, and enhancing alertness. However, when the coffee bean was processed in the form of green coffee bean (GCB) extract, it has an unpleasant flavour and limitations instability, activity, and bioavailability. This study aimed to produce microcapsules of the GCB (Coffea canephora) ethanolic extract containing considerable amounts of the bioactive compounds for nutraceutical supplements. The GCB ethanolic extract was microencapsulated by spray drying using a whey protein concentrate (WPC) biopolimer. The particle size (PSA), morphology (SEM), and physicochemical characteristics (UV and LC-MS/MS), as well as radical scavenging activity (DPPH) of the microcapsule were determined. We found that the microencapsulation yield was 95.85% of the extract, with the particle mean of volume diameter was 1.312 µm (span value: 1.285 µm). The morphology of microcapsule particles was irregular microspheres with dense, smooth, wrinkle and shrivel, compact, and homogeneous surface. The microcapsule demonstrated the caffeine content of 15.25%, the CGA content of 8.52%, the total phenolic content of 1794.7 ± 77.0 mg GAE/100g and the radical scavenging activity of 179.23 µg/mL. The WPC can be used to encapsulate the GCB extract by using spray drying microencapsulation to produce a high yield microcapsule with a smaller and narrower particle diameter. This microencapsulation was able to engulf and package unpleasant flavor and aroma, and to preserve considerable amounts of the bioactive compounds.